An Analysis of Guitar Performance Techniques in Sakura Theme and Variation by Yuquijiro Yocoh - Gabriel Ricky Sukrido (Repertoar, 2026)
This study aims to describe the classical guitar playing techniques in Yuquijiro Yocoh’s Sakura Theme and Variations and to explain their application and supporting factors, with a primary focus on these techniques in this work. This study is divided into seven sections: Introduction, Theme, Variation 1, Variation 2, Variation 3, Variation 4, and finally Coda. These sections feature several techniques, including guitar-playing techniques for the right and left hands. The right-hand techniques include appoggiando, tirando, pizzicato, tremolo, and strumming. The left-hand techniques include slur, barre, and harmonic.